Visualizing orbital angular momentum of plasmonic vortices - Shen, Z. (2013)
Plasmonic vortices (PVs) are generated by focusing a radially polarized optical vortex (OV) beam onto a metal surface. The intensity distribution of the PV is registered with a near-field scanning optical microscopy and agrees well with a theoretical prediction as well as numerical calculation. Beside the dark central spot, the numerical calculation also shows an azimuthal Poynting vector belonging to the PV, implying that the orbital angular momentum (OAM) was transferred from the radially polarized OV. To directly verify the OAM, plasmonic trapping experiments with gold micrometer particles are performed and the particle rotation is visualized. Further experiments by varying the topological charge of radially polarized OVs show the corresponding changes in rotation in terms of speed and radius.